Screening of Brazilian sugarcane genotypes for smut reaction - Lívia Maria Lemos Hoepers; Lucimeris Ruaro; João Carlos Bespalhok Filho; Ricardo Augusto de Oliveira; Henrique da Silva Silveira Duarte (Ciência Rural, 2023)
ABSTRACT: The main method of sugarcane smut (Sporisoriumscitamineum)control is the genetic resistance. This study assessed the reaction of Brazilian sugarcane genotypes to the smut. The design used was randomized blocks, with 41 genotypes and four replications. The experimental unit consisted of five seedlings per genotype. The genotypes were inoculated by immersing the buds in a smut spores’ suspension. For each genotype, it was obtained the disease incidence in percentage of stalk with whip and with the disease incidence data over time the area under the disease progress curve (AUDPC) were calculated for each genotype. Based in the AUDPC, three genotypes were classified as highly resistant (7.3%), eighteen as resistant (43.9%), twelve as moderately resistant (29.3%), three as moderately susceptible (7.3%) and five as susceptible (12.2%). Genotypes with higher levels of resistance to smut sugarcane can be used for integrated disease management and can be used as parents in new crosses in order to obtain progenies with higher proportion of genotypes resistant to smut.